2019
DOI: 10.1002/mrd.23148
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Prl7d1 causes placental defects at mid‐pregnancy in mice

Abstract: Prolactin family 7, subfamily d, member 1 (Prl7d1), a member of the expanding prolactin family, is mainly expressed in the placental junctional zone (including trophoblast giant cells and spongiotrophoblast cells) with peak expression observed at 12 days postcoitum (dpc) in mice. Previous studies have shown that PRL7D1 is a key mediator of angiogenesis in vitro; however, its physiological roles in placental development in vivo have not been characterized. To address this issue, we deleted Prl7d1 in mice and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that Prl −/− systemic knockout of Prl can affect the estrous cycle, leading to abnormal mammary gland development and infertility in female mice ( 24 ). Prl7d1 −/− knockout can lead to the thickening of the placental decidual spiral artery, resulting in reduced litter size and decreased fertility ( 25 , 44 ). Prlr −/− knockout can lead to female infertility and failure of progesterone production by the corpus luteum of the ovary in mice, leading to pregnancy failure ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Prl −/− systemic knockout of Prl can affect the estrous cycle, leading to abnormal mammary gland development and infertility in female mice ( 24 ). Prl7d1 −/− knockout can lead to the thickening of the placental decidual spiral artery, resulting in reduced litter size and decreased fertility ( 25 , 44 ). Prlr −/− knockout can lead to female infertility and failure of progesterone production by the corpus luteum of the ovary in mice, leading to pregnancy failure ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prl1a1 knockout results in female mice infertility ( 24 ). Prl7d1 −/− knockout results in smaller litter size ( 25 ). In adult mice, rabbits, and pigs, hyperprolactinemia stimulates uterine glandular hypertrophy ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…A progenitor invasive trophoblast subpopulation (Mm_TGC-Prog) was enriched for Ascl2, Ldoc1, and Prdm1 36 , interstitially invasive glycogen trophoblast (Mm_TGC_Gly) was enriched in Arid3a , and endovascularly invasive spiral artery-remodeling giant cells (Mm_TGC-SpA) expressed the prolactins Prl2a1 and Prl7b1 . Lastly, noninvasive sinusoidal giant cells (Mm_TGC_S) were marked by Prl2c2, Prl3b1 , and Prl7d1 37 , and canal giant cells (Mm_TGC_C) were marked by Hand1 and Prl2c1 .…”
Section: Placental Cell Type Homology and Eutherian Radiation Of Inva...mentioning
confidence: 99%
“…Targeted deletion of the prolactin-related genes Prl4a1 [54] and Prl7b1 [55] have minor effects on the placenta under normal conditions but major effects in response to stressors such as hypoxia. Targeted deletion of Prl7d1 results in a reduction of the labyrinth and gain in the junctional zone with a sex specific increase in the number of glycogen cells in the male placenta [56]. Placental hormone levels can be manipulated en mass through the genetic modification of imprinted genes which regulate the number of placental cells expressing hormones [57].…”
Section: Regulation Of Placental Hormone Production By Imprinted Genesmentioning
confidence: 99%